المشاركة المتناقصة وتطبيقاتها في المصارف السودانية: دراسة مقارنة - خيري، مرتضى عبدالله (جامعة الكويت - مجلس النشر العلمي, 2024)
الأهداف: تهدف هذه الدراسة إلى بيان أحكام صيغة المشاركة المتناقصة وتطبيقاتها في المصارف السودانية، ومعرفة صورها وخصائصها وما يترتب عليها من آثار اقتصادية، ومعرفة الدور الريادي الذي تؤديه في دفع عملية التنمية الاقتصادية والاجتماعية. المنهج: اعتمد على المنهج الوصفي التحليلي وكذا المقارن، وذلك بإيراد النصوص الفقهية في المذاهب الفقهية الأربعة ومقارنتها بنصوص قانون المعاملات المدنية السوداني لسنة ۱۹۸٤م وقانون الشركات السوداني لسنة ١٩٢٥م، النتائج: يمكن تلخيص أبرز نتائج الدراسة بما يأتي: ١- هناك قصور في تعريف الشركة في قانون المعاملات المدنية لسنة ۱۹۸٤م الذي حصرها في شركة العقد فقط، ۲- فقهاء المذاهب الفقهية لم يوردوا تعريفاً للمشاركة المتناقصة. 3- جواز عقد المشاركة المتناقصة اتساقاً مع ما توصل إليه مجمع الفقه الإسلامي، ووفقاً لمعايير هيئة المحاسبة والمراجعة للمؤسسات المالية الإسلامية. الخاتمة: خلصت الدراسة إلى ضرورة تعديل المادة ٢٤٦ من قانون المعاملات المدنية لسنة ١٩٨٤م الخاصة بتعريف الشركة لتشمل شركة الملك وشركة العقد معاً، وذلك بتبني تعريف وضوابط مجمع الفقه الإسلامي للمشاركة المتناقصة مع إدخال بعض التعديلات، وإصدار تشريع ينظم وسائل الاستثمار بالمشاركة والمشاركة المتناقصة المنتهية بالتمليك كوسائل استثمارية جنباً إلى جنب مع الوسائل الأخرى، وضرورة إعداد نشرات علمية متخصصة وعمل محاضرات وندوات ومؤتمرات لتوضيح هذه الوسيلة، والإجابة عما قد يعتريها من الشبهات. وقدمت الدراسة بعض التوصيات والاقتراحات بشأن المشاركة المتناقصة وتطبيقاتها في المصارف السودانية. Objectives: This study aims to explain the legal requirements of the Diminishing Mushārakah formula and its applications in Sudanese banks, and to know its forms and characteristics and its resulting economic effects and to know the pioneering role it plays in the advancement of the economic and social development process. Approach: It was based on descriptive, analytical and comparative approaches, presenting the doctrinal texts of the four schools of Islamic doctrine and comparing them with the texts of the Sudanese Civil Transactions Law of 1984 AD and the Sudanese Companies Act 1925 AD. Findings: The most salient findings of the study can be summarized as follows: 1- There is a gap in the definition of company in the Civil Transactions Act, 1984 AD, which limited it to contract company only. Jurisprudential schools have not provided a definition of a Diminishing Mushārakah. 3- It is permissible to enter into a Diminishing Mushārakah in accordance with the findings of the Islamic Fiqh Academy and in accordance with the standards of the Accounting and Auditing Organization for Islamic Financial Institutions. Conclusion: The study concluded that there is a need to amend Section 246 of the Civil Transactions Act, 1984 AD regarding the definition of company to include together jointly owned company and contract company, by adopting the definition and controls of the Academy of Islamic Jurisprudence for Diminishing Mushārakah with the introduction of some amendments and the adoption of legislation regulating the means of investment by participation and the Diminishing Mushārakah leading to ownership as a means of investment alongside other means, and the need to pre-pare specialized scientific publications and organize conferences, seminars and conferences to clarify this method and answer any doubts that may arise on this subject. The study presented some recommendations and suggestions regarding Diminishing Mushārakah and its applications in Sudanese banks.
Keywords: المؤسسات المالية -- الأحكام الفقهية -- قانون المعاملات المدنية -- السودان